2018
DOI: 10.1089/vim.2018.0042
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus Lytic Reactivation Induces IgG4 Production by Host B Lymphocytes in Graves' Disease Patients and Controls: A Subset of Graves' Disease Is an IgG4-Related Disease-Like Condition

Abstract: Immunoglobulin (Ig) G4-related disease (IgG4-RD) is a newly recognized systemic fibroinflammatory disease with characteristic histological findings and high serum IgG4 levels. Epstein–Barr virus (EBV) is a persistent herpesvirus in B lymphocytes, and we previously reported EBV reactivation-induced Ig production. We showed that EBV reactivation induced the production of thyrotropin receptor antibodies, the causative antibodies of Graves' disease. In the present study, we investigated whether EBV reactivation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
12
1
2
Order By: Relevance
“…However, the coincidence of EBV with low IgG4 levels in group I would contradict observations presented in the work of Nagata et al [17] in which the authors suggested that EBV-affected lymphocytes are stimulated to produce IgG4. It should be noted, however, that in the case of this research, the studied subjects were affected by Graves' disease-in which the stimulation of IgG4 production is a separate phenomenon.…”
Section: Discussioncontrasting
confidence: 57%
“…However, the coincidence of EBV with low IgG4 levels in group I would contradict observations presented in the work of Nagata et al [17] in which the authors suggested that EBV-affected lymphocytes are stimulated to produce IgG4. It should be noted, however, that in the case of this research, the studied subjects were affected by Graves' disease-in which the stimulation of IgG4 production is a separate phenomenon.…”
Section: Discussioncontrasting
confidence: 57%
“…We found that EBV(+) lymphocytes and IgG4(+) plasma cells accumulated in the same area in 7 out of 11 resected thyroid tissue samples from Graves' disease patients [66]. These findings indicated that IgG4 was produced under the influence of EBV-reactivation in local thyroid tissue.…”
Section: Ubiquitous Ig Productionmentioning
confidence: 67%
“…Evidence of an association between autoimmune thyroid diseases (AITD) and viral infections is, however, emerging. (5)(6)(7)(8)(9)(10)(11)(12). Still, the evidence linking viral infection to disease development is limited and direct investigation of thyroid tissue for evidence of antiviral responses has rarely been undertaken.…”
Section: Introductionmentioning
confidence: 99%